2016
DOI: 10.1016/j.aap.2015.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of fatal train-pedestrian collisions in metropolitan Chicago 2004–2012

Abstract: The paper analyzes spatial and temporal data on fatal train-pedestrian collisions in the Chicago metropolitan area between 2004 and 2012. In comparing different municipalities within the region, the density of grade crossings and stations is found to increase the frequency of unintentional deaths. However, unintentional deaths do not increase with train volume suggesting that pedestrians may exercise more care around busier lines. The distribution of apparent intentional deaths is less strongly related to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
(26 reference statements)
1
8
1
Order By: Relevance
“…The analysis of detailed incident data (provided by 12 countries) showed for example that (a) victims were predominantly males, both for suicides and trespassing accidents, (b) victims were typically between 20 and 59 years of age, (c) railway suicides and trespassing accidents seem to be fairly evenly distributed throughout the year, (d) all weekdays are represented quite evenly, and (e) suicides were almost always committed by persons alone, and even in trespassing accidents there was seldom more than one victim. These data are comparable with the ones published in recent works by Mishara and Bardon in Canada [10], Savage in USA [11], Too et al in Australia [12], and Uittenbogaard and Ceccato in Europe [13]. However, as pointed out by Mishara and Bardon [10], it is unfortunate that data from Europe are not available from lower income countries and the few reports that exist describe only a few incidents in a specific area, making generalisation difficult.…”
Section: Data On Railway Suicides and Trespasssupporting
confidence: 69%
See 1 more Smart Citation
“…The analysis of detailed incident data (provided by 12 countries) showed for example that (a) victims were predominantly males, both for suicides and trespassing accidents, (b) victims were typically between 20 and 59 years of age, (c) railway suicides and trespassing accidents seem to be fairly evenly distributed throughout the year, (d) all weekdays are represented quite evenly, and (e) suicides were almost always committed by persons alone, and even in trespassing accidents there was seldom more than one victim. These data are comparable with the ones published in recent works by Mishara and Bardon in Canada [10], Savage in USA [11], Too et al in Australia [12], and Uittenbogaard and Ceccato in Europe [13]. However, as pointed out by Mishara and Bardon [10], it is unfortunate that data from Europe are not available from lower income countries and the few reports that exist describe only a few incidents in a specific area, making generalisation difficult.…”
Section: Data On Railway Suicides and Trespasssupporting
confidence: 69%
“…Furthermore, the toolbox is continuously maintained and updated by UIC, therefore its contents are ever expanding and improving as new studies are published (see for e.g. [10][11][12][13]). …”
Section: Organisation and Contentmentioning
confidence: 99%
“…Intentional deaths are more prevalent on lines with frequent passenger trains. 35 Events usually occur close to home. 8,36 Higher rates of suicides were found when stations were crowded, when there were faster trains and when high-risk groups were attracted to these stations.…”
Section: Geography Of Railway Suicidesmentioning
confidence: 99%
“…Savage, 2016 [24] December has the most trespasser injuries of all months, and June has the least. Patterson, 2004 [25] Day of week…”
Section: Monthmentioning
confidence: 99%
“…When analyzing the times of such occurrences, current findings can be organized into the time of year, day of the week or date. In terms of the time of year, some studies have found that such collisions are more likely to occur in spring and summer, possibly as a result of increased outdoor pedestrian activities [16,24]. However, a study in Finland found no difference among the twelve months [18].…”
Section: Introductionmentioning
confidence: 99%